2015
DOI: 10.1088/0004-637x/809/1/73
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution of Quasi-Separatrix Layers and Active Region Upflows

Abstract: Persistent plasma upflows were observed with Hinode's EUV Imaging Spectrometer (EIS) at the edges of active region (AR) 10978 as it crossed the solar disk. We analyze the evolution of the photospheric magnetic and velocity fields of the AR, model its coronal magnetic field, and compute the location of magnetic null-points and quasisepratrix layers (QSLs) searching for the origin of EIS upflows. Magnetic reconnection at the computed null points cannot explain all of the observed EIS upflow regions. However, EIS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 64 publications
3
35
0
1
Order By: Relevance
“…Our model includes also a transformation of coordinates from the local AR frame to the observed one (see Démoulin et al 1997), so that the computed field lines can be directly compared to the observed loops. For more details about how the computational box is selected and its size controlled, see Mandrini et al (2015). Typical coronal conditions imply that the magnetic field is force free and frozen into the plasma almost everywhere in solar ARs.…”
Section: The Local Magnetic-field Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model includes also a transformation of coordinates from the local AR frame to the observed one (see Démoulin et al 1997), so that the computed field lines can be directly compared to the observed loops. For more details about how the computational box is selected and its size controlled, see Mandrini et al (2015). Typical coronal conditions imply that the magnetic field is force free and frozen into the plasma almost everywhere in solar ARs.…”
Section: The Local Magnetic-field Modelmentioning
confidence: 99%
“…We infer the direction in which reconnection proceeds from the observed event evolution (see e.g. Mandrini et al 2015, and references therein). In Fig.…”
Section: Bps In Ar 10484mentioning
confidence: 99%
“…It is commonly believed that it is due to that the emission optical depth increases with the emission frequency to the square (Benz 1993). On the other hand, the range of type-I chains (below ∼400 MHz) shows that these chains are generated at upper parts of the active-region loops located close to the quasi-separatrix layers of the active region as proposed by Mandrini et al (2015).…”
Section: New Model Of Type-i Chainsmentioning
confidence: 80%
“…However, type-I chains are observed in metric range and DPSs in decimetric range, that is, in different altitudes of the solar atmosphere with different densities, different density gradients and magnetic field strengths. Moreover, while DPSs are usually observed during the impulsive phase of eruptive flares (Nishizuka et al 2015), type-I chains are a part of noise storms connected with the reconnection activity at the quasi-separatrix layer in the active region (Mandrini et al 2015).…”
Section: Comparison Of Chains Of Type-i Radio Bursts and Drifting Pulmentioning
confidence: 99%
See 1 more Smart Citation